Experimental investigation on the heat transfer performance and pressure drop characteristics of γ-Al2O3/water nanofluid in a double tube counter flow heat exchanger - B. Raei; F. Shahraki; M. Jamialahmadi; S.M. Peyghambarzadeh (Transport Phenomena in Nano and Micro Scales, 2016)
In this paper, overall heat transfer coefficient and friction factor of water based γ-Al2O3 nanofluid in a double tube counter flow heat exchanger have been measured experimentally under turbulent flow condition. For better dispersion of γ-Al2O3 nanoparticles in distilled water, magnetic stirrer and ultrasonic vibrator (with a power of 240 kW and frequency of 35 kHz) were implemented. The stabilized γ-Al2O3 /water nanofluid have been examined at the concentrations of 0.05 and 0.15 vol. % with variation of flow rates in the range of 7–9 l/min. Nanofluid enters the inner tube of the heat exchanger at different temperatures including 45, 55,and 65 °C. Results demonstrated that increasing the nanofluid flow rate, concentration and inlet temperature can improve the overall heat transfer coefficient and heat transfer rate. Also, the ratio of the overall heat transfer coefficient of nanofluid to that of pure water decreased with increasing the nanofluid flow rate. Meanwhile, the maximum enhancements of the overall heat transfer coefficient and heat transfer rate and friction factor compared with those of base fluid (distilled water) are respectively equal to 19.3%, 10% and 25% which is occurred at the concentration of 0.15 vol. %.